MALDI mass spectrometry for identification lactic acid bacilli isolated from lactic acid products produced in the Karaganda region - Amirkhanova, Zh.; Bodeeva, R.; Akhmetova, S.; Tuyakova, A.; Kozhakhmetov, S.; Kushugulova, A. (KU Publ., 2021)
At present the traditional methods of identifying microorganisms are replaced by express methods, the mass spectrometric method using MALDI-TOF MS allows to reliably identify a variety of microorganisms in a short time, which is an indisputable advantage in work and allows to quickly identify many microorganisms in quickly. Classical methods for the identification of lactic acid bacteria based on their cultivation require a long time for their implementation. The advent of matrix laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) technology made significant changes in the workflows for the study of lactic acid bacteria, unmatched in speed characteristics. This article presents the study of the morphological, cultural properties, acid-forming ability, antibiotic sensitivity lactic acid bacteria of isolated from ... products (ayran, koumiss, ashykan kozhe, kurt, suzbe, cottage cheese) produced in different districts of the Karaganda region. The species identification of the isolated strains of lactic acid bacteria was carried out using a MALDI-TOF mass spectrometer. The studies carried out on cultural and morphological characters indicate that they belong to the genus Lactobacillus, Lacticaseibacillus, Lactiplantibacillus, Limosilactobacillus. As a result of identification on the mass spectrometer of the presented samples L. acidophilus (2 strains), L. delbrueckii subsp. bulgaricum (2 strains), L. rhamnosus (7 strains), L. plantarum (2 strains), L. paracasei (11 strains), L. fermentum (2 strains) were revealed. According to the Score values, the results indicate the accuracy of the identification.
Қарағанды облысында өндірілетін сүтқышқылды өнімдерден бөлініп алынған сүтқышқылды бациллаларды идентификациялау үшін малди масс-спектрометрияны қолдану
МАЛДИ масс-спектрометрия для идентификации молочнокислых палочек, выделенных из молочнокислых продуктов, производимых в Карагандинской области
Keywords: lactic acid bacilli; strain; identification; cultivation; mass spectrometry (MALDI-TOF MS); dairy products; morphology; nutrient medium